Identifying risk and mitigating gambling-related harm in online poker. Issue 3 (4th March 2018) - Parke, Adrian; Griffiths, Mark D.
Abstract : The present paper conducts a critical analysis of the potential for gambling-related harm in relation to online poker participation, and a theoretical evaluation of current responsible gambling strategies employed to mitigate harm in online gambling and applies the evaluation of these strategies specifically to online poker gambling. Theoretically, the primary risk for harm in online poker is the rapid and continuous nature of poker provisions online, and has been demonstrated to be associated with disordered gambling behaviour, including the chasing of monetary losses. The following responsible gambling features were deemed relevant for consideration: informed player choice, voluntary self-exclusion, employee intervention, pre-commitment, in-game feedback, behavioural tracking tools, and age restriction and verification. Although current responsible gambling features are evaluated as theoretically robust, there remains a fundamental need for experimental validation of their effectiveness. Furthermore, despite online poker gamblers perceiving the responsible gambling features as valuable tools, in reality very few players regularly use available responsible gambling features. Ultimately, for the online poker gambling industry to retain market credibility and avoid substantial top-down regulation, it is imperative to demonstrate effectiveness of responsible gambling approaches, and increase customer utilisation of available harm-mitigation features.